COLLECTION AND PROCESSING OF DATA FOR THE RISK ASSESSMENT SYSTEM DURING TRAVELING - Адаменко, Павел; Левченко, Андрей; Шугайло, Юрий (SWorldJournal, 2021)
The paper deals with the problem of safe travel. As a solution to this problem, a support and decision-making system is provided that can optimize the route from a safety point of view